Culinary delights from the dream of the chief mechanic of the corvette “Zubr” D. D. Guslikov from Sukhumi on 18 July 1858 - Morozowa, Olga (Perspektywa stołu, 2023)
Nutrition is one of the most important components of material living conditions, and their level – one of the indicators of human well-being. After analyzing the diet, we can assess not only the taste preferences of its representative, but also his financial situation, status and possibilities.The aim of the article is to draw attention to dreams as a specific method of getting to know everyday life, as well as the private life of certain strata of the population of the Russian Empire of the 19th century, in particular the nutritional properties and material well-being of the lower ranks of the navy.In the 19th century, the Russian Empire developed its own culinary traditions regarding food preferences, food intake rules, table design, etc., which are different for certain categories of society. The representatives of maritime professions also had their own traditions. Their research and analysis are of particular interest.Based on the sleep analysis of chief mechanic D.D. Guslikov, seen by him in Sukhumi on July 18, 1858, as well as an analysis of scientific literature, the author describes the daily life, diet and material well-being of the lower ranks of the Russian Empire in the second half of the 19th century.